Pemberdayaan Peternak melalui Pemanfaatan Limbah Produksi Tempe sebagai Pakan Probiotik untuk Mendukung Efisiensi dan Keberlanjutan Usaha - Ahadiah Agustina; Abdul Wahab; Suhairin; Ageska Nugroho; Baiq Andini (BALE LITERASI, 2026)
The availability of affordable and quality feed remains one of the challenges to the sustainability of livestock farming, while tempe production waste in the partner community has not been optimally utilized. This community service activity aimed to empower livestock farmers through the utilization of tempe production waste as a probiotic feed ingredient while improving their skills in producing more efficient and sustainable feed. The activity was conducted with Tempe De Batur MSME and Ternak De Solah through several stages, including socialization, training, demonstrations, hands-on practice, mentoring, and evaluation of participants’ knowledge and skills. The processing involved utilizing tempe production waste combined with locally available feed materials and a fermentation starter according to the applied formulation. The results showed that participants gained improved understanding of material selection, fermentation procedures, starter application, packaging, storage, and identification of suitable fermented feed characteristics. Participants were also able to independently practice processing tempe waste into fermented feed. The activity contributed to increasing the utilization of local resources, providing alternative feed materials, and strengthening collaboration between tempe producers and livestock farmers to support a circular economy. Therefore, utilizing tempe production waste as probiotic feed has potential as an empowerment strategy to improve feed efficiency and support the sustainability of livestock businesses.